Surgery, chemoradiotherapy, or chemoradiation plus immunotherapy: Treatment strategies for nonmetastatic anal squamous cell carcinoma - Fang He; Mo Chen; Qi-jun Yao; Zhi-min Liu; Yandong Zhao; Fengyun Pei; Jian Zheng; Yuan-hong Gao; Jun Huang (Translational Oncology)
The current standard of care for anal squamous cell carcinoma (ASCC) is definitive concurrent chemoradiotherapy (CRT). However, about a third of patients may experience treatment failure. Recently, immunotherapy has emerged as a novel strategy for metastatic ASCC patients. We evaluated the efficacy and safety of surgery, CRT alone, and CRT with immunotherapy (CRT-I) in 100 nonmetastatic ASCC patients, treated from April 2012 through May 2023, by determining survival outcomes and acute adverse events. The median (range) follow-up was 30.7 (7.6 to 134.9) months. The study cohort 3-year overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS), and locoregional recurrence-free survival (LRFS) rates were 80.7 %, 62.2 %, 71.1 %, and 67.6 %, respectively. The Surgery group had significantly lower rates than the CRT and CRT-I groups for 3-year PFS (33.1% vs. 65.2% vs. 92.9 %, P < 0.001), DMFS (46.7% vs. 74.6% vs. 92.9 %, P = 0.002) and LRFS (37.0% vs. 73.3% vs. 92.9 %, P < 0.001), respectively. All patients receiving CRT-I were alive at last follow-up. Of 100 patients, 26 (26.0 %) experienced severe (≥ grade 3) acute toxicity. Of 24 patients receiving CRT-I, 8 (33.3 %) had severe acute toxicity. Using immunohistochemistry, peritumoural stromal infiltration by CD8+ T cells was significantly higher after CRT-I compared to before CRT-I and to after CRT alone. The addition of immunotherapy to CRT may be an effective first-line treatment option with favourable survival outcomes and acceptable toxicity for patients with ASCC. A prospective, randomized trial assessing the efficacy of CRT combined with a PD-1 inhibitor in patients with locally advanced ASCC is in progress.